HUBUNGAN ANTARA POSISI TUBUH DENGAN KELUHAN MUSKULOSKELETAL PADA PETANI PADI DI DESA SILONGO KECAMATAN LUBUK TAROK KABUPATEN SIJUNJUNG - Niswatun Fauziah; Darwin Karim; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Safety at working area is still largely ignored by worker. Musculoskeletal complain is the most frequent complain. The aim of this research was to identify the correlation between the position of the body and incidence of musculoskeletal disorders in farmers at village Silongo subdistrict Lubuk Tarok. The design was descriptive correlation research with cross sectional approach. The sampling technique was purposive sampling with inclusion criteria is not having a disability in the musculoskeletal system, working period> 1 year and age 20-60 years, willing to be a respondent involving 60 respondents. This research used nordic body map (NBM) sheets and observation sheets used Rapid Entire Body Assessment (REBA) that has been validity and reliability. The univariate analysis used to determine the frequency distribusion and the bivariat analysis used Chi-Square test. The results showed that there was a significant relationship between the position of the body and musculoskeletal disorders between body position with musculoskeletal complain on farmers with p value (0.006) <α (0.05). Based on this result, farmers should be more knowing about the right position of body to reduce musculoskeletal complain.Keywords: Body position, complaint, farmers, musculoskeletal